(untitled) (International Journal of Engineering and Computer Science, 2018)
The objective behind making this project deals out with satisfying various functional needs such as secretly spying or keeping surveillance over a desired target location. We also aim to achieve a few more additional comprehensive needs such as detection of gas, temperature sensing, camouaging feature and movement of bot. We have made our robot with an advantage of monitoring both audio and video parameters. The most eye catching feature of our bot is that it would be able to change its body colour that it treads along. We have achieved our main goal by aggregating individual robotic functions in a single robotic package. This bot can either be used for keeping an eye or a supervisory control function like a spy bot or with the additional features as that we have added to this robot could serve as an important unmanned vehicle which could actually combat with the opponents or enemies in the war _elds. Thus making it multifunctional, it could be used to serve more than one application areas. The camouaging feature of bot is solution for reducing human losses in military operations or terrorist attacks. This project is basically a step taken to save the human lives in the area where this bot is used.